A (in)constitucionalidade da comunicabilidade de bens particulares dos cônjuges na sucessão - Seganfredo, Ricardo Fabrício (2022)
The present work analyzes the constitutionality and legality of succession competition between spouse and descendants. The wording and current interpretation of the Superior Court of Justice (STJ) of article 1,829, item I, of Brazilian Civil Code, make it impossible for an individual to keep his private patrimony unharmed in the face of the succession of the spouse. Through a deductive method and bibliographic research technique, the law is analyzed intrinsically and extrinsically. The study was divided into three parts. The first presents the main patrimonial aspects of family law. In the second, the study of the history and principles relating to property regimes and their succession consequences is deepened. In the third part, an intrinsic analysis is initially carried out, approaching the norm from the internal point of view of private law and, then, from an external point of view. The conclusion is that the wording of article 1,829, I, of the Brazilian Civil Code carries vices that make it incompatible with the internal logic of the law to which it is a part, infringing principles such as private autonomy and objective good faith. From the external point of view, the provision suffers from constitutionality, as it affronts human dignity and equality, elementary principles provided for in the Constitution of the Federative Republic of Brazil of 1988.